A LOAN FROM EGYPT? THE "INNERSPIKE LUTE" IN AFRICA - (:unkn) unknown (My University, 2007)
According to the usual typology, the handle of the spike-lute does not go all the way through the body of the instrument but terminates close to a hole in the skin which covers the instrument. The strings passing through this hole are tied to the other end of the handle with laces. I will provide data and hypotheses on the origins of this lute, as well as on its geographical distribution and diffusion in Africa, in comparison with that of harps and lyres.
Keywords: African Research